PENGARUH PENDEKATAN PEMBELAJARAN MATEMATIKA REALISTIK (PMR) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII SMPN 1 DUA KOTO KABUPATEN PASAMAN - Nurlaili, Nurlaili; Fitri, Dewi Yuliana; Yusri, Radhya (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2023)
This research is motivated by the low ability of students to solve math problems in learning mathematics. The purpose of this study was to find out whether students' mathematical problem solving abilities after being applied a realistic mathematics learning approach (PMR) were better than students' mathematical problem solving abilities before being applied a realistic mathematics learning approach (PMR) in class VIII students at SMP N 1 Dua Koto, Pasaman Regency. This type of research is a pre-experimental study with a One Group Pretest-Postest design. The population of this study were all students of class VIII SMP Negeri 1 Dua Koto, Pasaman Regency. The technique used in this research is purposive sampling. The sample chosen for this study was class VIII 2. The research instrument used was the pre-test and post-test in the form of a description test. Furthermore, testing the hypothesis using the t test. Based on the data analysis carried out, it was obtained t_count = 10.297 and t_table = 1.71, because t_count>t_table then reject H_0 at a significant level of 0.05 so it can be concluded that whether students' mathematical problem solving abilities after being applied a realistic mathematics learning approach (PMR) were better than students' mathematical problem solving abilities before being applied a realistic mathematics learning approach (PMR) in class VIII students at SMP N 1 Dua Koto, Pasaman Regency.